How does the concentration of spatial allocation of urban construction land across cities affect carbon emission intensity in China? - Hui Yang; Cheng Chen; Jingye Li; Min Li; Stefan Sieber; Kaisheng Long (Ecological Indicators)
Optimizing the spatial allocation of urban construction land (UCL) from the national perspective and promoting its moderate concentration are imperative prerequisites for synergistically accomplishing economic growth and carbon emission reduction goals. However, how the concentration of spatial allocation of urban construction land (CSA) across cities influences carbon emission intensity (CEI) remains unclear. To bridge this knowledge gap, we investigated the impact of CSA on CEI in 282 cities in China by using multi-source panel data (e.g., urban carbon emissions data, construction land area data, and socio-economic data) from 2005 to 2020 and applying econometric models: fixed effect model, mediating effect model, and spatial Durbin model. The results revealed that CSA exhibited a significant and robust U-shaped effect on CEI. During the study period, the proportion of cities crossing the inflection point slightly decreased from 57.80 % in 2005 to 55.67 % in 2020, and their spatial distribution pattern remained relatively stable. It is predicted that this proportion will drop to 53.90 % in 2030, and the average CEI of these cities will decrease by 67.93 % from 2005 to 2030. In this scenario, China’s carbon emission reduction target for 2030 can be attained in the sampled cities. The heterogeneity analysis showed that the impact of CSA on CEI followed a U-shaped pattern in both the developed and developing regions, as well as in the eastern, central and western regions. Additionally, the analysis revealed a similar pattern in both the resource- and non-resource-based cities. Conversely, this impact was significantly positive in the northeastern region. The mediating effect analysis suggested that CSA indirectly influenced CEI through economic agglomeration (EA), technological innovation (TI), and industrial structure upgrading (ISU). The spatial spillover effect analysis demonstrated that CSA exerted a U-shaped effect on CEI in neighboring regions through the spatial spillover effect. The geographical extent of this effect depends on the geographical distance between cities and their gross domestic product per capita. These findings provide reference values for the spatial allocation and scale control of UCL, and carbon reduction in countries whose UCL allocation and land planning are primarily controlled by the government.